The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11661-014-2198-0
|View full text |Cite
|
Sign up to set email alerts
|

Creep and Stress Relaxation Anisotropy of a Single-Crystal Superalloy

Abstract: In this study, the TMF stress relaxation and creep behavior at 1023 K and 1223 K (750°C and 950°C) have been investigated for a Ni-based single-crystal superalloy. Specimens with three different crystal orientations along their axes were tested; h001i, h011i, and h111i, respectively. A highly anisotropic behavior during TMF stress relaxation was found where the h111i direction significantly shows the worst properties of all directions. The TMF stress relaxation tests were performed in both tension and compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Compared to creep test data, stress relaxation data for superalloys is sparse [1,2,[8][9][10] and especially rare for single crystal alloys [2,9,10]. Test durations at constant strain beyond 24 h are essential for a higher fidelity design of the high temperature seals, but such data are absent.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to creep test data, stress relaxation data for superalloys is sparse [1,2,[8][9][10] and especially rare for single crystal alloys [2,9,10]. Test durations at constant strain beyond 24 h are essential for a higher fidelity design of the high temperature seals, but such data are absent.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not believed that the serrated yielding occurs due to twinning in this case. Instead, previous studies [10,11] have reported of a serrated yielding behaviour for the 011 direction, and it was discussed that dynamic strain ageing has occurred and also that only one slip system is active during plastic deformation in the 011 direction. If a serrated yielding behaviour during the first cycles will influence the TMF life has not been considered in this paper, but this may be of interest for future research.…”
Section: The Tmf Behaviourmentioning
confidence: 98%
“…These components are often cast from nickel-base superalloys in the form of singlecrystals. The material anisotropy of single-crystal materials adds an extra dimension of complexity to the modelling, testing and understanding of the fracture mechanisms [3][4][5][6][7][8][9][10][11]. The service life of many hot components is not fully restricted by the number of cycles to crack initiation, which means that a certain amount of crack propagation is allowed before the component has to be replaced in service.…”
Section: Zusammenfassungmentioning
confidence: 99%